Why Not Crime Prevention? An Evidence-based Perspective - Monchalin, Lisa (Criminologie)

(untitled) (Les Presses de l’Université de Montréal, 2022)
This paper gives an overview of the literature on effective crime prevention and its implementation. Scientific evaluations of crime prevention projects that tackle risk factors often reveal that they reduce crime and are often more efficient at doing so than standard criminal justice responses. Inter-governmental organizations agree on the critical steps necessary to mobilise relevant agencies to tackle such risk factors. Despite recommendations by parliamentary committees and a growing number of experts, effective crime prevention has not achieved the prominent role that it could occupy in order to more effectively reduce rates of crime in Canada. However, the recent policy announcement by the province of Alberta may offer some ways in which this resistance might eventually be overcome.